Exploring grade 11 learners' intra-mathematical connections when solving trigonometric equations - Phele, Elizabeth Chuene (My University, 2023)
This study explored the intra-mathematical connections that Grade 11 learners make when solving trigonometric equations. The study was conducted in a high school in Mankweng Circuit. A qualitative case study design was used in this study to describe intra-mathematical connections and meaning learners made when solving trigonometric equations. Data were collected through observations, documents and interviews. During the lessons I was a participant observer, meanwhile documents accessed were in the form of activities and test. Interviews were semi-structured which allowed me to get more information about the intra-mathematical connections learners made and how they affected them when solving trigonometric equations. Data were analysed thematically. The findings showed that learners made intra-mathematical connections of procedural, different representations, part-whole and meaning type. It was also found that the type of intra-mathematical connections learners made in their solution process allowed most of them to follow appropriate procedures, for visualisation of the trigonometric equations and determine solutions as angles in specific intervals. Therefore, the study recommends that the understanding of mathematical concepts can be developed through the skill of making mathematical connections which are highlighted by a network of nodes and links represented by mathematical topics and concepts.
Thesis (M.Ed. (Mathematics Education)) -- University of Limpopo, 2023
Keywords: Grade 11 learners; Intra-Mathematical connections; Trigonometric equations; Eleventh grade (Education); Equations; Trigonometry; Education, Secondary -- South Africa -- Limpopo; Trigonometry -- Problems, exercises, etc.; Mathematics -- Study and teaching